Congratulations! Tribute to Professor Dr. Ulrike Wanitzek (2020)
With this collage the Africa Multiple Cluster of Excellence wants to pay tribute to one of its founding members, Prof. Dr. Ulrike Wanitzek who received the University Medal of the University of Bayreuth in November 2019. On behalf of all the members of the Africa Multiple Cluster of Excellence and everybody involved in African Studies at the University of Bayreuth: Congratulations, Professor Wanitzek! (C) Song by Matchume Zango for the Africa Multiple Cluster of Excellence